MORPHOLOGICAL AND KARYOLOGICAL STUDY OF THE SPECIES OF THE FAMILY $GERANIACEAE$ JUSS. OF ARMENIAN FLORA (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
In connection with taxonomic study of representatives of the Geraniaceae family of Armenian flora. Usually during the species identification the structure of the root system, life form, leaf morphology, flower structure, inflorescence, carpels structure are taken into account. The karyological research of the genus Geranium growing in Armenian flora has revealed the following: for 8 species we discovered diploid and tetraployid cytoraces. The basic chromosome numbers х = 9, 10, 13, 14 shows up in the genus Geranium.
Keywords: $Geranium$; $Erodium$; morphological characteristics; chromosomes numbers; kariotype; submetacentric chromosomes; metacentric chromosomes; cytorace